2010
DOI: 10.1007/s00268-010-0542-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Surgical Informed Consent: Past, Present, and Future. A Quest to Help Patients Make Better Decisions

Abstract: BackgroundInformed consent (IC) is a process requiring a competent doctor, adequate transfer of information, and consent of the patient. It is not just a signature on a piece of paper. Current consent processes in surgery are probably outdated and may require major changes to adjust them to modern day legislation. A literature search may provide an opportunity for enhancing the quality of the surgical IC (SIC) process.MethodsRelevant English literature obtained from PubMed, Picarta, PsycINFO, and Google betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
171
0
20

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(192 citation statements)
references
References 87 publications
1
171
0
20
Order By: Relevance
“…Our study identified considerable deficiencies in the current knowledge and attitudes of our doctors toward this very crucial area of doctor-patient communication. Surprisingly certain studies from institutions in the western countries such as the USA, Europe, Netherlands and New Zealand have also reported a lack of doctors' knowledge regarding the process of SIC (1,3,(7)(8)(9)(10). Less than ideal level of working knowledge and attitudes regarding SIC on part of our doctors indicates a case for their focused education regarding SIC.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Our study identified considerable deficiencies in the current knowledge and attitudes of our doctors toward this very crucial area of doctor-patient communication. Surprisingly certain studies from institutions in the western countries such as the USA, Europe, Netherlands and New Zealand have also reported a lack of doctors' knowledge regarding the process of SIC (1,3,(7)(8)(9)(10). Less than ideal level of working knowledge and attitudes regarding SIC on part of our doctors indicates a case for their focused education regarding SIC.…”
Section: Discussionmentioning
confidence: 95%
“…The additional gains with the use of computer programs for SIC would include better structure, improved quality, diminished consultation time and stimulated patient commitment. The time and effort saved for busy surgeons can better used for answering specific queries and concerns of the patient in brief consultation sessions with the patients (1,21,22). In our study majority of doctors admitted that they did not employ any structured proforma for the SIC.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…6 Indeed, there is increasing support for such Web-based consent interventions within the field of surgery. 7 Such Web sites could deliver information in an accessible, lowliteracy manner in order to facilitate an informed decision-making process for prospective living liver donors.…”
mentioning
confidence: 99%